2014
DOI: 10.1007/s00280-014-2437-5
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming oxaliplatin hypersensitivity: different strategies are needed according to the severity and previous exposure

Abstract: Attention should be paid to patients with any prior exposure to oxaliplatin, especially during early chemotherapy cycles. Given the high success rate of preventing HSR by desensitization administration and its apparent safety profile, we suggest that desensitization be considered as the first option for the treatment of grades 3 and 4 HSR cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Accordingly, in Japanese FOLFOX-treated patients, HSRs occurred at 9 (4–16) cycles [ 7 ] and 9 (2–15) cycles [ 9 ], grade-1/2 HSRs occurred at 8.4 ± 4.4 cycles and grade-3/4 HSRs occurred at 9.3 ± 3.9 cycles [ 13 ]. In addition, using data from 156 and 17 patients who experienced HSRs during FOLFOX and XELOX therapies, respectively, Lee et al [ 21 ] reported that HSRs occurred at earlier cycles in the latter group of patients (6.6 ± 0.3 versus 3.1 ± 0.6 cycles). Although HSRs occurred earlier in their FOLFOX therapy group as compared to that in our study, the observed earlier occurrence of HSRs in the XELOX therapy group is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in Japanese FOLFOX-treated patients, HSRs occurred at 9 (4–16) cycles [ 7 ] and 9 (2–15) cycles [ 9 ], grade-1/2 HSRs occurred at 8.4 ± 4.4 cycles and grade-3/4 HSRs occurred at 9.3 ± 3.9 cycles [ 13 ]. In addition, using data from 156 and 17 patients who experienced HSRs during FOLFOX and XELOX therapies, respectively, Lee et al [ 21 ] reported that HSRs occurred at earlier cycles in the latter group of patients (6.6 ± 0.3 versus 3.1 ± 0.6 cycles). Although HSRs occurred earlier in their FOLFOX therapy group as compared to that in our study, the observed earlier occurrence of HSRs in the XELOX therapy group is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be highlighted that a more recent publication by the same group, concluded that premedication resulted in a lower success rate in the prevention of HSRs associated with oxaliplatin. Namely, only 71.6% of patients who received premedication had partial or complete prevention of HSRs and were able to continue their treatment [25]. Moreover, Bhargava et al [60] and Brandi et al [13] reported that premedication is not always effective.…”
Section: Steroids and Antihistaminesmentioning
confidence: 97%
“…Lee et al [25] presented the results of a retrospective study concerning oxaliplatin-induced HSRs. These reactions occurred at 6.3 ± 0.3 mean chemotherapy cycle.…”
Section: Incidencementioning
confidence: 99%
“…3,16 Densensitization protocols have also been employed successfully. [16][17][18] However, despite these interventions, reactions have still occurred.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3,16 Densensitization protocols have also been employed successfully. [16][17][18] However, despite these interventions, reactions have still occurred. Prior to making her decision to cease adjuvant chemotherapy, our patient was made fully aware of the options for continuing oxaliplatin-based chemotherapy and the potential risk of further serious and even fatal HSR even with preventative strategies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%